(3CQHYjf GdeSGhGIs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3CNHQfG GdGTHGM GdSGOg GHh GSMb GHQGgje Hf CHj WGgQ CeG HYO aEf Gdgd SHMGfg deG GNJU GdGeGe QVi GdaQjbjf ef GdQJH HChaGgG hNU GHG YHO Gddg eMeO Hf GdaVd GdMOjK GdChd adeG QLYJ Edi QShd Gddg Udi Gdgd Ydjg hSde hGNHQJg HGdPi UfYJ abGd EfeG cs
(3BNQgG (B:s
(3GNHQfi jhfS Yf GdRgQi Yf CHj Sdeg Yf YGFTI QVi Gdgd YfgG Yf GdfHi Udi Gddg Ydjg hSde (B" (3bGd dG haGdfPQ ai eYUjg Gddg hcaGQJg caGQg jejf hgPG BNQ GdGQHYjf s
(3GdfSNI HgG MhGTs
(3HgG SeGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B54s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs